The Influence of Work Environment, Work Stress, Workload on Turnover Intention Through Organizational Commitment as an Intervening Variable - Muhammad Teguh Herwidiyanto; Lijan Poltak Sinambela (International Journal of Economics and Management Sciences, 2024)
Research was conducted to analyze the effect of work environment, work stress, workload on turnover intention through organizational commitment. Sampling based on purposive sampling technique as many as 120 respondents with the criteria of project logistics division employees at PT Pos Logistics. The results concluded that the work environment has a negative and significant effect on turnover intention; work stress and workload have a positive and significant effect on turnover intention. The effect of organizational commitment as an intervening variable shows that the work environment has a negative and significant effect on turnover intention; work stress price and workload have a positive and significant effect on turnover intention.